The Nordic Expert Group for Criteria Documentation of Health Risks from Chemicals. 146. Polychlorinated biphenyls (PCBs) - Lindell, Birgitta (Gothenburg, 2012)
"Polychlorinated biphenyls (PCBs) are a class of 209 synthetic compounds (con-geners), in which 1–10 chlorine atoms are attached to biphenyl in different com-binations. PCBs are non-volatile, although low-chlorinated congeners have a much higher vapour pressure than high-chlorinated. All PCBs are lipophilic and some are very persistent. For environmental reasons, PCB production and use is nowadays banned or restricted worldwide. PCBs were produced as mixtures with very dif-ferent compositions, consisting of ~ 70–100 congeners with dioxin-like PCBs as minor constituents. They were used e.g. as hydraulic oils, as cooling liquids in electrical equipment and in building materials including elastic sealants. Food of animal origin (e.g. fatty fish) is the main source of environmental PCB exposure. Occupational exposure to PCBs may occur e.g. during renovation work and handling of waste but also in PCB-contaminated buildings such as schools and offices. Limited data indicate that occupationally exposed in the Nordic countries have slightly elevated total PCB plasma/serum levels as compared to pre-exposure values or to control groups. The increase compared to controls may at least in part be due to historical occupational exposure. The total PCB levels in workers are still within the range of those measured in the general population during the last two decades. The plasma/serum concentrations of certain PCB congeners can be used as markers of occupational exposure. As total PCB plasma/serum levels in occupationally exposed seem to be in the same range as those of the general population, their health risks are presumably similar. Studies on the general population suggest that PCB mixtures may slightly affect sperm motility and possibly contribute to an increased risk for non-Hodgkin’s lymphoma. In offspring, PCB exposure may contribute to subtle developmental changes including neurobehavioural effects (e.g. on cognition), effects on im-mune system, and, possibly, birth weight. Yet, co-exposure to other pollutants hampers interpretation of the data. Many of the effects seen in humans have also been reported in animals. The effects of PCB mixtures in animals occurring at the lowest dose levels (5–7.5 ?g/ kg bw/day) are effects on reproduction (resorptions/foetal death) and development (e.g. neurobehavioural effects), immune system, skin/nails and eyelids. Thyroid effects and effects on male fertility have been reported at higher doses, and cancer only at much higher doses. Many of the effects have been attributed primarily to dioxin-like congeners. The most potent dioxin-like PCB congener, PCB 126, has been classified by IARC as a human carcinogen based on animal and mechanistic data. Some data suggest that the non-dioxin-like PCB congeners are important for the neurobehavioural effects in offspring. Keywords: Aroclor, cancer, developmental, diabetes, fertility, immunotoxicity, non-Hodgkin’s lymphoma, occupational exposure limit, PCB, polychlorinated biphenyls, reproductive, review, risk assessment, thyroid, toxicity."